State and intellectual in imperial Japan : - Barshay, Andrew E. (University of california Press, 1989)
In this superbly written and eminently readable narrative, Andrew E. Barshay presents the contrasting lives of Nanbara Shigeru (1889-1974) and Hasegawa Nyoze-kan (1875-1969), illuminating the complex predicament of modern Japanese intellectuals and their relation to state and society. Following the Meiji Restoration of 1868, a powerful modern state began to emerge in Japan, and with it, the idea of a "public" sphere of action. This sphere brought with it a new type of intellectuala "public man" whose role was to interpret and nationalize "universal" (and largely foreign) ideas and ideologies. Activity within the public sphere took many forms as Japanese intellectuals sought to define their changing roles. At no time was such public activity as intense as during the crisis years of later imperial and early postwar Japan. In contrasting case studies, Andrew E. Barshay presents the lives of two modern Japanese intellectuals, Nanbara Shigeru (1889-1974), professor of Western political thought at Tokyo Imperial University, and Hasegawa Nyozekan (1875- 1969), a versatile independent journalist.